Creating competitive advantage through stakeholder management? A study of French private clinics - FREGIER, Gael (2016)
Today the general consensus on stakeholder management is that it creates value for firms as it favours stakeholders’ engagement and loyalty. However, it is not clear how big a value stakeholder management creates. Indeed, the literature on the link between stakeholder management and competitive advantage is relatively scarce and there is no clear conclusion. This paper examines whether stakeholder management can provide a competitive advantage to French private clinics. The sector has been purposefully chosen for the heterogeneity of stakeholder groups within this wider public industry. We investigated how clinics manage the different stakeholder’s claims and to what extent stakeholder management can generate a competitive advantage. We adopted a qualitative method to investigate the topic, conducting semi-structured interviews with clinics’ managing directors, middle managers, physicians and investors. Our findings reveal that in order to face the economic pressure due the steadily reduction of medical fees, cooperation between clinics, hospitals, institutional agencies and physicians has become necessary. In this context stakeholder management has become a requirement that can provide an ‘early stage’ competitive advantage through a better market positioning, the recruitment of valuable resources and the generation of capabilities. However, in the long run, this competitive advantage becomes null as the regulatory environment eventually lead to an inter-firm homogeneity. Furthermore, this ‘early stage’ competitive advantage could turn into a competitive disadvantage as the costs and the time involved in managing all stakeholder’s claims – especially in a sector where cut reduction is a priority - outweigh the benefits from a stakeholder approach.